Influence of Fishing Technique on Organochlorine Pesticide Accumulation in Fish and its Possible Human Health Risk in the Republic of Be´nin - AHOYO, THEODORA ANGÈLE; YEHOUENOU AZEHOUN PAZOU, ELISABETH (My University, 2013)
In Benin different techniques are used for large-scale commercial fishing, Acadjas (enclosures constructed in the river) and Whe´dos (holes made in the river banks). This study aimed at assessing the extent of contamination related to these fishing techniques. Fish contained residues of DDT and its metabolites, a-endosulfan, dieldrin, aldrin, endrin and lindane. Pesticide levels were similar in fish from Acadjas and Whe´dos, except for higher a-endosulfan levels in fish from the Whe´dos. Comparing pesticide intake levels through fish consumption with tolerable daily intake levels showed that in all cases risk for human health is low.
Keywords: Human health risk Organochlorine; pesticides Fish culture techniques Human exposure